Proceedings of the International Conference of Mechatronics and Cyber-MixMechatronics - 2018 - Gheorghe, Gheorghe I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This proceedings book gathers contributions presented at the 2nd International Conference of Mechatronics and Cyber-MixMechatronics/ICOMECYME, organized by the National Institute of R&D in Mechatronics and Measurement Technique in Bucharest, Romania, on September 6th-7th, 2018. Further, it reflect the expansion of the field of Mechatronics, which has yielded newer trans-disciplinary fields including Adaptronics, Integronics, and Cyber-Mix-Mechatronics. These are also the topics addressed by the respective book chapters. The conference has a rich scientific tradition and attracts specialists from all over the world - including North America, South America, and Asia. ICOMECYME is focused on presenting research results and is mainly directed at academics and advanced students, but also offers a venue for interacting with R&D experts. These proceedings will especially benefit entrepreneurs who want to invest in research and who are open for collaborations. .
Keywords: Mechatronics; Computational intelligence; Mechatronics; Computational Intelligence